(untitled) - Baker, R. Jacob (Piscataway, NJ,Hoboken, NJ, 2008)
CMOS: Circuit Design, Layout, and Simulation, Revised Second Edition covers the practical design of both analog and digital integrated circuits, offering a vital, contemporary view of a wide range of analog/digital circuit blocks, the BSIM model, data converter architectures, and much more. This edition takes a two-path approach to the topics: design techniques are developed for both long- and short-channel CMOS technologies and then compared. The results are multidimensional explanations that allow readers to gain deep insight into the design process
Keywords: Metal oxide semiconductors, Complementary,Integrated circuits,Metal oxide semiconductor field-effect transistors,Mạch liên kết; Design and construction,Design and construction,Thiết kế và xây dựng